Anteseden kebahagiaan pada anak prasekolah - Izzaty, Rita Eka; Ayriza, Yulia (Jurnal Psikologi Ulayat, 2024)
This study aimed to test the construct of children’s happiness based on situations and parties that make children happy. The instrument is developed based on previous qualitative research in the form of multiple choices statements using smiling emoticons of different sizes. The subjects were 88 children aged 4-6 years in Sleman, Yogyakarta. Results of exploratory factor analysis show that the antecedent of children’s happiness based on situations is composed of eight factors--doing useful activities, fun activities, entertaining situations, getting attention/things liked, family gathering, and drawing. The parties who play a role in children's happiness are their closest parties (mother, siblings, and God), their closest surrounding environment (father and friends), and other close environment outside nuclear family. Our findings can be used as a reference to measure children's happiness in the Indonesian context so that strategies can be designed to increase children's happiness through effective policies, educational practices, and parenting.